(untitled) (American Journal of Islam and Society, 2006)
The subject of child detention is fraught with complexities of both a legal and an emotional nature, particularly when placed in the context of conflict. Founded on the Defence for Children International: Palestine Section’s (DCI/PS) work conducted between 1999 and 2003, the contributors developed a level of expertise in the realm of youth detention in Israeli prisons through research, advocacy work, and the experiences of their colleagues, many of whom were former child detainees. The result is a compelling and often disquieting read, replete with testimonies by the children, their families, and lawyers which relates the unforgiving conditions and obstacles that clutter the legal process and place the child at a disadvantage. Edifying and cogent, the authors maintain an objective narrative throughout, thereby enabling the reader to absorb the circumstances and legal framework prior to constructing an independent conclusion. In addition, the tables, graphs, and figures corroborate and clarify such subjects as Israeli position abuse (shabeh), the characteristics of prisons, and key terms related to human rights and humanitarian law, as well as a glossary that provides background information concerning the noted organizations, statutes, and terminologies ...